Role of change management in the successful roll-out of IT projects: a case study of higher learning institutes in Malaysia - Qadri, Mehran; Khalid Hussain, Mohammad; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
Change is inevitable. This is especially true in our modern society where change occurs more rapidly than before. Change management has now become a critical part of any organization. Organizations that were world leaders five or six years ago are nowhere to be seen because they failed to adopt to change. However, adopting change is not an easy task and involves a multitude of factors that must be considered before any change takes place. Fortunately, there are a lot of models/methodologies available that cater to the needs of change within an organization. This paper reviews four popular change management methodologies for the context of this study, i.e., the role of change management in the successful roll out of IT projects at Malaysian Institutes of Higher Learning (IHLs). This paper also considers the objectives of the Malaysian Education Blueprint (MEB) proposed by the Ministry of Higher Education. This paper finally suggests a change management methodology that is best suited for implementing required changes related to IT projects at IHLs.